Perception of other healthcare professionals about the nurses' role and competencies in veno‐venous extracorporeal membrane oxygenation care: A qualitative study - Muna Alshammari; Chitra Vellolikalam; Sadiq Alfeeli (Wiley, 2022)
Abstract Aim This study aimed to explore the perception of other healthcare professionals, including the doctors, physiotherapists and perfusionists, about the nurses' role and competencies in veno‐venous extracorporeal membrane oxygenation. Background Extracorporeal membrane oxygenation is considered as a challenging clinical activity that requires critical decision and rapid response from nurses, particularly in emergencies. It was observed that nurses are primarily responsible for bedside management of these patients, and teamwork was found helping the nurses to manage this high‐acuity care. However, little is known on the perception of other healthcare professionals about the nurses' roles and competencies, which would contribute to further improvements in quality extracorporeal membrane oxygenation care. Design This was a qualitative descriptive study. Methods One‐to‐one in‐depth interviews were conducted with nine healthcare professionals working in extracorporeal membrane oxygenation care in an adult intensive care unit of a general hospital in Kuwait. Results Participants reported that nurses play critical and multiple roles and responsibilities in the insertion, maintenance, weaning, and retrieval of extracorporeal membrane oxygenation, plus providing general nursing care, and performed their roles competently. Heavy workload, less recognition and support, and individual differences in competence were reported as possible barriers to the nurses' performance. Conclusion Other healthcare professionals recognize continuous training, having experience, teamwork, and increased staffing as measures that can promote the nurses' role in extracorporeal membrane oxygenation.